The neurobiology of sign language and the mirror system hypothesis - Emmorey, Karen (2013)
I suggest two puzzles for the Mirror System Hypothesis. First, there is little evidence that mirror neuron populations for words or for signs exist in Broca’s area, and a mirror system is not critical for either speech or sign perception. Damage to Broca’s area (or to the mirror system for human action) does not result in deficits in sign or speech perception. Second, the gesticulations of speakers are highly integrated with speech, but pantomimes and modern protosigns (conventional gestures) are not co-expressive with speech, and they do not co-occur with speech. Further, signers also produce global, imagistic gesticulations with their mouths and bodies simultaneously while signing with their hands. The expanding spiral of protosign and protospeech does not predict the integrated and co-expressive nature of modern gestures produced by signers and speakers.